IMPLEMENTASI CULTURALLY RESPONSIVE TEACHING (CRT) DAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR - Jannah, Aprita Nur; Azizah, Izza; Haris Rosyidi, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
To study mathematics, different learning strategies are needed to motivate students to learn. Integrating local culture into the learning process is also important for students to understand the connection between concepts and the surrounding culture. This research was conducted to improve student learning outcomes by implementing the Culturally Responsive Teaching (CRT) approach and the Teams Games Tournament (TGT) learning model, aided by the snakes and ladders media, on the topic of flat-sided space shapes in class VII J of SMPN 2 Candi. The type of research conducted is classroom action research (CAR). This study is a type of descriptive research that utilizes the Kemmis & McTaggart model.. It consists of two cycles, each with four stages: planning, acting, observing, and reflecting. The results of the first cycle showed an improvement in learning outcomes to 43.75%, and the number of students who had not yet achieved the learning objectives decreased by 6. In the second cycle, learning outcomes improved to 100%, with all students meeting the learning objectives. The implementation of the CRT approach and the TGT model using snakes and ladders media effectively improved student learning outcomes on the topic of flat-sided space shapes in mathematics class VII J of SMPN 2 Candi.